Promoting sustainability competency and self-efficacy in class teacher education - Karvonen, Roosa; Ratinen, Ilkka; Kemi, Ulla (Frontiers in Sustainability, 2023)
There is an urgent need for a global sustainability transition. This change needs to be cultural and transform both our actions and the values on which we base our decision-making. Sustainability transition requires concentrating on future generations as well as on the people teaching them because class teachers have an impact on their pupils’ knowledge, skills, values, and attitudes. Therefore, class teachers need new competency to make sustainability transformation in schools happen. Teachers also need to possess a sufficient level of self-efficacy beliefs, as they strongly impact a teacher’s ability to manage their job as a sustainability educator. This survey research studied Finnish class student teachers’ (N=166) perceptions about their sustainability competency and self-efficacy in education for sustainable development. Students’ perceptions of their sustainability competency were clustered into one weighted sum variable. Three principal components were constructed with principal component analysis (PCA) to describe the students’ self-efficacy beliefs in education for sustainable development. A PCA paired with linear hierarchical regression analysis was conducted to explain the variation in students’ sustainability competency perceptions. The results indicated that the combined self-efficacy beliefs in teaching values and ethics and systems thinking explained 19.3% of the variation in class student teachers’ sustainability competency. As a result, improving class student teachers’ self-efficacy beliefs about teaching ethics and values and systems thinking in the Finnish context can improve their sustainability competency and vice versa. To promote the sustainability competency of class student teachers, it is necessary to be aware of this connection when developing class teacher education.